Solution by extracting a root

🏆Practice extracting square roots

Solution by extracting a root

Solving a quadratic equation with one variable of the form X2c=0X^2-c=0 (where b=0b=0) by taking the square root:

First step

Moving terms and isolating X2X^2.

Second stage

Take the square root of both sides. Don't forget to put ±\pm before the square root of the free term.

Third stage

Writing solutions in an organized manner or writing "no solution" in case of a root of a negative number.

Start practice

Test yourself on extracting square roots!

einstein

Solve for X:

\( x\cdot x=49 \)

Practice more now

Solution by extracting a root

Pay attention -
This solution method is suitable for quadratic equations where there is no bb, and Y=0Y=0, meaning quadratic equations that look like this:
Y=x2+cY=x^2+c
For example:
X2+4=0X^2+4=0
In equations of this type, we won't need to use the quadratic formula or other long methods, and we can use an efficient and quick way - taking the square root!

How do we solve it?

Let's learn through an example.
Let's solve together the equation:
x216=0x^2-16=0

First step:

Let's move terms and isolate x2x^2 so it will be alone on one side (even without a coefficient).
Let's perform:
x2=16x^2=16

Second stage:

Let's take the square root of both sides and remember to put ±± because when taking the square root of a free number there are 22 opposite solutions (one negative and one positive)
Let's solve:
x=±4x=±4

Third stage:

Let's write the answers we got in an organized way.
We will perform:
X1=4X_1=4
X2=4X_2=-4

Excellent! Now we'll continue practicing solving equations with one variable 11, increase the difficulty level and encounter different cases.

Exercise with coefficient greater than 11 for x2x^2:
3x29=03x^2-9=0

Solution:
Let's start by completely isolating x2x^2. We'll perform:
3x2=93x^2=9
x2=3x^2=3

Now, after we completely isolated x2x^2, we can take the square root of both sides. Let's not forget to put the ±\pm sign
Let's solve:
x=±3x=±\sqrt3
Let's write the answers in an organized way:
X1=3X_1=\sqrt3
X2=3 X_2= -\sqrt3

Exercise requiring finding the square root of a negative number:
X2+4=0X^2+4=0

Solution:
First, we'll move terms to isolate X2X^2
We'll perform:
x2=4x^2=-4
Now we need to find the square root as usual. But!! We cannot find the square root of a negative number!
This means that there is no number that when squared will give us a negative result.
Therefore when we try to find the square root:
X=(4)X=\sqrt{(-4)}
The answer will be - no solution!
Note! If you leave the answer like this
X=(4)X=\sqrt{(-4)}
it would be a mistake. You must write - no solution. Square root of a negative number cannot be found.

Another exercise:
12x2240=012x^2-240=0

Solution:
At first glance, this exercise might look a bit intimidating because its numbers are relatively large. However, we can solve exercises like these easily using the method we've learned so far.
First, we'll completely isolate x2x^2 .
We'll perform:
12X2=24012X^2=240
We'll divide both sides by 1212 and get:
x2=20x^2=20
Now we'll take the square root and not forget the ±\pm sign
We'll perform:
X=±20X=±\sqrt{20}
We'll write both answers in an organized way:
X1=20X_1=-\sqrt{20}

X2=20X_2=\sqrt{20}

Another exercise:
3x2+150=03x^2+150=0

Solution:
First, let's move terms to get:
3x2=1503x^2=-150
Now let's divide both sides by 33 to completely isolate X2X^2.
We get:
X2=50X^2=-50
At this point, we can already see that the equation has no solution because it's impossible for any number squared (whether positive or negative) to give us a negative number like 50-50.
Nevertheless, let's continue to show there's no solution and try to take the square root.
We get:
x=±(50)x=±\sqrt{(-50)}
The answer will be - no solution since we cannot take the square root of a negative number.

Important note –
Sometimes students get confused and tend to think there is only 11 solution to the equation, the solution of the ++.
This is a serious mistake since we still need to find the square root of 5050- and not of 5050, therefore we won't get any solution when we need to find the square root of a negative number.

Exercise with a fractional result:
3X24=03X^2-4=0

Solution:
First, we'll move terms to get:
3x2=43x^2=4
Now we'll divide both sides by 33 to get:
x2=43x^2=\frac43
Note, don't be alarmed by getting a fraction, we'll continue as usual. The next step is to take the square root. We get:
x=±43x=±\sqrt{\frac43}
And we'll write the results in an organized way:
X1=43X_1=\sqrt{\frac43}
X2=43X_2=-\sqrt{\frac43}

Important note - when a square root can be easily simplified, like for the number 16\sqrt{16} for example, you should not leave the answer like that and write 44.
However, if you cannot get a whole number square root, it is usually fine to leave the answer with the square root.

Join Over 30,000 Students Excelling in Math!
Endless Practice, Expert Guidance - Elevate Your Math Skills Today
Test your knowledge

Examples with solutions for Extracting Square Roots

Exercise #1

Solve for X:

xx=49 x\cdot x=49

Video Solution

Step-by-Step Solution

We first rearrange and then set the equations to equal zero.

x249=0 x^2-49=0

x272=0 x^2-7^2=0

We use the abbreviated multiplication formula:

(x7)(x+7)=0 (x-7)(x+7)=0

x=±7 x=\pm7

Answer

±7

Exercise #2

Solve the following exercise:

2x28=x2+4 2x^2-8=x^2+4

Video Solution

Step-by-Step Solution

First, we move the terms to one side equal to 0.

2x2x284=0 2x^2-x^2-8-4=0

We simplify :

x212=0 x^2-12=0

We use the shortcut multiplication formula to solve:

x2(12)2=0 x^2-(\sqrt{12})^2=0

(x12)(x+12)=0 (x-\sqrt{12})(x+\sqrt{12})=0

x=±12 x=\pm\sqrt{12}

Answer

±12 ±\sqrt{12}

Exercise #3

Solve the following equation:

x216=x+4 x^2-16=x+4

Video Solution

Step-by-Step Solution

Please note that the equation can be arranged differently:

x²-16 = x +4

x² - 4² = x +4

We will first factor a trinomial for the section on the left

(x-4)(x+4) = x+4

We will then divide everything by x+4

(x-4)(x+4) / x+4 = x+4 / x+4

x-4 = 1

x = 5

Answer

5

Exercise #4

x2x=0 x^2-x=0

Video Solution

Step-by-Step Solution

The equation in the problem is:

x2x=0 x^2-x=0

First let's note that in the left side we can factor the expression using a common factor, the largest common factor for the numbers and letters in this case is x x and this is because the first power is the lowest power in the equation and therefore is included both in the term with the second power and in the term with the first power, any power higher than this is not included in the term with the first power, which is the lowest, and therefore this is the term with the highest power that can be factored out as a common factor from all terms in the expression, so we'll continue and perform the factoring:

x2x=0x(x1)=0 x^2-x=0 \\ \downarrow\\ x(x-1)=0

Let's continue and address the fact that in the left side of the equation we got in the last step there is a multiplication of algebraic expressions and on the right side the number 0, therefore, since the only way to get 0 from multiplication is to multiply by 0, at least one of the expressions in the multiplication on the left side must equal zero,

meaning:

x=0 \boxed{x=0}

or:

x1=0x=1 x-1=0\\ \downarrow\\ \boxed{x=1}

Let's summarize then the solution to the equation:

x2x=0x(x1)=0x=0x=0x1=0x=1x=0,1 x^2-x=0 \\ \downarrow\\ x(x-1)=0 \\ \downarrow\\ x=0 \rightarrow\boxed{ x=0}\\ x-1=0 \rightarrow \boxed{x=1}\\ \downarrow\\ \boxed{x=0,1}

Therefore the correct answer is answer B.

Answer

x=0,1 x=0,1

Exercise #5

Solve for x:

x281=0 x^2-81=0

Video Solution

Step-by-Step Solution

Let's solve the given equation:

x281=0 x^2-81=0 Note that we can factor the expression on the left side using the difference of squares formula:

(a+b)(ab)=a2b2 (\textcolor{red}{a}+\textcolor{blue}{b}) (\textcolor{red}{a}-\textcolor{blue}{b})=\textcolor{red}{a}^2-\textcolor{blue}{b}^2 We'll do this using the fact that:

81=92 81=9^2 Therefore, we'll represent the rightmost term as a squared term:

x281=0x292=0 x^2-81=0 \\ \downarrow\\ \textcolor{red}{x}^2-\textcolor{blue}{9}^2=0 If so, we can represent the expression on the left side in the above equation as a product of expressions:

x292=0(x+9)(x9)=0 \textcolor{red}{x}^2-\textcolor{blue}{9}^2=0 \\ \downarrow\\ (\textcolor{red}{x}+\textcolor{blue}{9})(\textcolor{red}{x}-\textcolor{blue}{9})=0 From here we'll remember that the product of expressions equals 0 only if at least one of the multiplied expressions equals zero,

Therefore, we'll get two simple equations and solve them by isolating the variable in each:

x+9=0x=9 x+9=0\\ \boxed{x=-9} or:

x9=0x=9 x-9=0\\ \boxed{x=9}

Let's summarize the solution of the equation:

x281=0x292=0(x+9)(x9)=0x+9=0x=9x9=0x=9x=9,9 x^2-81=0 \\ \downarrow\\ \textcolor{red}{x}^2-\textcolor{blue}{9}^2=0 \\ \downarrow\\ (\textcolor{red}{x}+\textcolor{blue}{9})(\textcolor{red}{x}-\textcolor{blue}{9})=0 \\ x+9=0\rightarrow\boxed{x=-9}\\ x-9=0\rightarrow\boxed{x=9}\\ \downarrow\\ \boxed{x=9,-9} Therefore, the correct answer is answer B.

Answer

x=±9 x=\pm9

Start practice